2018
DOI: 10.1021/acs.estlett.8b00274
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Reverse Osmosis for Energy-Efficient Hypersaline Brine Desalination: Current Status, Design Considerations, and Research Needs

Abstract: Water scarcity, expected to become more widespread in the coming years, demands renewed attention to freshwater protection and management. Critical to this effort are the minimization of freshwater withdrawals and elimination of wastewater discharge, both of which can be achieved via zero liquid discharge (ZLD), an aggressive wastewater management approach. Because of the high energetic cost of thermal desalination, ZLD is particularly challenging for high-salinity wastewaters. In this review, we discuss the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(151 citation statements)
references
References 66 publications
1
149
0
1
Order By: Relevance
“…While RO is significantly more efficient than thermal, phase-changebased desalination technologies such as multi-effect-distillation, its application to the desalination of high salinity brines (typically 70 000 ppm and above) is limited by the high hydraulic pressures required. 6,121,122 Novel high-salinity RO-based process designs, such as osmotically assisted RO [123][124][125] and low salt rejection RO, 126 have the potential to reduce the hydraulic pressure required to achieve high brine salinities, expanding the applicability of RO to minimal-and zero-liquid discharge processes. [127][128][129] Further work is required to overcome key challenges, including internal concentration polarization and optimal membrane spacer design, that have thus far limited the practical realization of processes in which both sides of the membrane are in contact with saline streams.…”
Section: Pressure-driven Desalinationmentioning
confidence: 99%
See 1 more Smart Citation
“…While RO is significantly more efficient than thermal, phase-changebased desalination technologies such as multi-effect-distillation, its application to the desalination of high salinity brines (typically 70 000 ppm and above) is limited by the high hydraulic pressures required. 6,121,122 Novel high-salinity RO-based process designs, such as osmotically assisted RO [123][124][125] and low salt rejection RO, 126 have the potential to reduce the hydraulic pressure required to achieve high brine salinities, expanding the applicability of RO to minimal-and zero-liquid discharge processes. [127][128][129] Further work is required to overcome key challenges, including internal concentration polarization and optimal membrane spacer design, that have thus far limited the practical realization of processes in which both sides of the membrane are in contact with saline streams.…”
Section: Pressure-driven Desalinationmentioning
confidence: 99%
“…Current RO membranes and membrane modules, however, lack the mechanical robustness required to overcome the osmotic pressures encountered during the treatment of hypersaline solutions. 6 Thermal-driven technologies have thus withheld applications in the desalination of brines, despite being inherently energy intensive due to the required vapor-liquid phase changes. To offset the large latent heat of vaporization, recent thermal-driven efforts have shifted towards the use of renewable energy sources-particularly solar.…”
Section: Introductionmentioning
confidence: 99%
“…With a corresponding NaCl rejection of 74%, the hydraulic pressure in the device (P root ) was therefore <−338 bar, an enormous negative pressure. For reference, conventional RO is typically limited to a maximum of ~80 bar (43).…”
Section: Hydrogel Leaf For Desalination Of Hypersaline Watermentioning
confidence: 99%
“…The rejection decrease can again be explained by low water flux ( fig. S6) and high salinities (30,(39)(40)(41)43). Design of a device with greater leaf area, relative to the root membrane area, would likely increase the flux and rejection.…”
Section: Hydrogel Leaf For Desalination Of Hypersaline Watermentioning
confidence: 99%
“…However, studies have reported severe deterioration of membrane performance during such high-pressure operations [15][16][17]. Although "high-pressure RO" has recently been proposed as an alternative to distillation-based methods for hypersaline brines [18], it is likely not a trivial challenge to design suitable high-strength membrane materials without compromising membrane transport properties. Additionally, implementation of mechanically robust membrane modules and system components to the high pressurizations will also likely require considerable capital cost.…”
Section: Introductionmentioning
confidence: 99%